2023
DOI: 10.1029/2023gl104766
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Salinity Anomaly Has Triggered the Recent Decline of Winter Convection in the Greenland Sea

Lucas Almeida,
Nicolas Kolodziejczyk,
Camille Lique

Abstract: The Greenland Sea is a key region for open ocean convection and ventilation, which exhibit a large variability with periods of strong convection and shutdowns. After a long period of weak winter convection (from the 1970s to the early 1990s), a recovery has been reported, beginning in the 1990s and intensifying in the early 2000s until 2013. Using ISAS, an optimal interpolation product based on Argo observations, we document a recent significant weakening of deep convection between 2014 and 2020, accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Extreme events are driving change faster than predictions (Almazroui et al, 2021;Tabari, 2020) and as a result, tipping points forecast for later in the century may be on the verge of breach. Already the increase of fires worldwide (Clarke et al, 2022;Pandey et al, 2023), and in the previously frozen Arctic Boreal forest (Dieleman et al, 2020, p. 202;Kim et al, 2020;Veraverbeke et al, 2017), the change in ocean salinity and overturning as a consequence of ice melt (Almeida et al, 2023;Boers, 2021;Ditlevsen & Ditlevsen, 2023;Fournier et al, 2023), and the switch of carbon sequestration to emission of the Amazon (Gatti et al, 2021;Lovejoy & Nobre, 2018) and Arctic tundra (de Vrese & Brovkin, 2021;Heffernan et al, 2020;Hugelius et al, 2020) have been reported (Figure 2).…”
Section: Cross-scale Changes Drive Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme events are driving change faster than predictions (Almazroui et al, 2021;Tabari, 2020) and as a result, tipping points forecast for later in the century may be on the verge of breach. Already the increase of fires worldwide (Clarke et al, 2022;Pandey et al, 2023), and in the previously frozen Arctic Boreal forest (Dieleman et al, 2020, p. 202;Kim et al, 2020;Veraverbeke et al, 2017), the change in ocean salinity and overturning as a consequence of ice melt (Almeida et al, 2023;Boers, 2021;Ditlevsen & Ditlevsen, 2023;Fournier et al, 2023), and the switch of carbon sequestration to emission of the Amazon (Gatti et al, 2021;Lovejoy & Nobre, 2018) and Arctic tundra (de Vrese & Brovkin, 2021;Heffernan et al, 2020;Hugelius et al, 2020) have been reported (Figure 2).…”
Section: Cross-scale Changes Drive Future Researchmentioning
confidence: 99%
“…For the past century, forests have consistently been, on balance, sinks for anthropogenic CO 2 , but studies show regions transitioning to sources due to more frequent and intense drought, warming and fire (Alves de Oliveira et al, 2021;Braghiere et al, 2023;Dieleman et al, 2020;Gatti et al, 2021;Lovejoy & Nobre, 2018;Massey et al, 2023;Wang et al, 2021). The stability of the Arctic and Antarctic regions are critical for global ocean and atmospheric circulation, and melting ice has already begun to shift ocean and atmospheric circulation (Almeida et al, 2023;Boers, 2021;Ditlevsen & Ditlevsen, 2023;Fournier et al, 2023). The thawing Arctic also has vast stores of at-risk carbon that could result in significant carbon emissions ( As the climate and socio-political conditions change, a growth in "megacities" creates unique opportunities for localized carbon emission management and, perhaps, sequestration in urban forests (Dodman et al, 2022;Wei et al, 2021).…”
Section: Cross-scale Changes Drive Future Researchmentioning
confidence: 99%